Pengaruh Brand Image dan Word of Mouth Terhadap Keputusan Pembelian di MR. DIY Aceh Barat - Bayu Irfandi; Chairiyaton Chairiyaton (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This research explores Brand Image and Word of Mouth on purchasing decisions at Mr. DIY West Aceh with research objectives to analyze and determine the influence between brand image, Word of Mouth and purchasing decisions. Using a correlational quantitative approach with 100 samples drawn using a non- probability sampling technique calculated using the lemeshow formula. The research results show that Brand Image (X1) has a significant influence on Purchasing Decisions (Y) at MR DIY, with a significance value (Sig.) of 0.000 which is smaller than 0.05, Word of Mouth (X2) has a significant influence on Purchasing Decisions (Y), with a significance value (Sig.) of 0.001 which is smaller than 0.05 and the F test results show that the regression model that combines Brand Image (X1) and Word of Mouth (X2) on Purchasing Decisions (Y) has a very significant influence, with an F value of 106.554 and a significance value of 0.000 < 0.05. Apart from this, it still needs to be improved by optimizing Word of Mouth and a more comprehensive marketing strategy.